“Originalism” of Interpretation in the United States Constitution - I Dewa Gede Palguna; Bima Kumara Dwi Atmaja (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Originalism is a viewpoint that is one of the methods and theories of constitutional interpretation. It remains controversial in its application, particularly in the decisions of the United States Supreme Court. Originalism first held that the interpretation of the United States Constitution must follow the original intent of the constitutional drafters or those who ratified it. However, in the 1990s, this stance changed, namely that the interpretation of the Constitution must follow the original meaning of the constitutional text. The aim of this research is to understand the anti-mainstream concepts of originalism interpretation. The fundamental problem lies not to answer which one is better between originalist and non-originalist. Instead, it rather depends on how to use this approach in several cases. It is possible that in one case using an originalist approach will be more relevant and appropriate, while in another case it will be absurd, and it is happened in several decisions in the United States. The Normative legal research method was used in this research with five major approaches. Those are the statute, conceptual, historical, casuistry, and comparative approaches. The result of this study indicates that: first, originalism is a stance directly related to perspective on the issue of interpretation of the Constitution. Meanwhile, the interpretation of the Constitution itself is an attempt to understand the definitions contained in the Constitution and the objectives it aims to achieve. Second, reflecting on the practice in the United States, the originalism approach may be more relevant on some occasions. However, originalism will be absurd if applied on other occasions because society has changed so much. Therefore, in such circumstances, getting out of originalism is a necessity.